Teaching and Assessing the English Passive Voice Inductively - Navas Brenes, César Alberto (2026)
This study examines the effect of inductive instruction in the acquisition of the English passive voice among a group of twenty-five EFL students. Although this target population takes the second course of the English major, this is the first-time learners study and assimilate the passive voice at this level. After administering a diagnostic instrument on such structure, the instructor observes the acquisition, progress, and usage of the passive voice in two types of written tasks throughout the course. At the end of the semester, students will take a second, non-graded instrument to assess the acquisition of the passive voice with the help of Task-based activities.